Joint Associations of Obesity and Cardiorespiratory Fitness With Coronary Artery Calcium Composition: IS THERE EVIDENCE FOR FAT-BUT-FIT?. Issue 3 (8th February 2022) - Jae, Sae Young; Kim, Hyun Jeong; Lee, Kyung Hyun; Kunutsor, Setor K.; Heffernan, Kevin S.; Choi, Yoon-Ho; Kang, Mira
Abstract : When examining the joint associations of obesity and cardiorespiratory fitness with indices of coronary artery calcification, the fit-obese combination was not associated with coronary artery calcification scores, which could potentially reinforce the fat-but-fit paradigm. Abstract : Introduction: The purpose of this study was to examine the individual and joint associations of obesity and cardiorespiratory fitness (CRF) with indices of coronary artery calcification (CAC) in 2090 middle-aged men. Methods: Obesity was defined as a body mass index (BMI) ≥25 kg/m 2 and a waist circumference (WC) ≥90 cm. Cardiorespiratory fitness was operationally defined as peak oxygen uptake (V˙o 2peak ) directly measured using gas analysis. Participants were then divided into unfit and fit categories based on age-specific V˙o 2peak percentiles. Agatston scores >100 and volume and density scores >75th percentile were defined as indices of CAC, signifying advanced subclinical atherosclerosis. Results: Obese men had increased CAC Agatston, volume, and density scores, while higher CRF was associated with lower Agatston and volume scores after adjusting for potential confounders. In the joint analysis, unfit-obese men had higher CAC Agatston and CAC volume. The fit-obesity category was not associated with CAC Agatston (OR = 0.91: 95% CI, 0.66-1.25, for BMI and OR = 1.21: 95% CI, 0.86-1.70, for WC) and CAC volume (OR = 1.14: 95% CI, 0.85-1.53, for BMI and OR = 1.23: 95% CI, 0.90-1.69, for WC), which were similar to estimates for the fit-normal weight category. Conclusions: These findings demonstrate that while obesity is positively associated with the prevalence of moderate to severe CAC scores, CRF is inversely associated with the prevalence of moderate to severe CAC scores. Additionally, the combination of being fit and obese was not associated with CAC scores, which could potentially reinforce the fat-but-fit paradigm.